Who learns more independently? Gender-based perspectives on English learning autonomy in university settings - Suryanto Suryanto; Diah Savitri; Turki Alsolami; Bolormaa Shinjee (Englisia: Journal of Language, Education, and Humanities, 2026)
This study investigated gender-based differences in English learning autonomy among Indonesian university students enrolled in an English Language Education Department. A total of 108 students (52 males, 56 females) participated in the study. Employing a quantitative research design, data were collected using a validated questionnaire that assessed six dimensions of learner autonomy. Descriptive statistics and an independent-samples t-test were used for data analysis. The findings revealed that male students demonstrated a moderate level of autonomy (M = 2.93), which was comparable to that of female students, who also exhibited a moderate level of autonomy (M = 2.89). The t-test indicated no statistically significant difference between genders (t(106) = 0.454, p = 0.650), with a small effect size (d = 0.09). These results suggest that gender does not function as a determining factor of learner autonomy within this specific educational context. Rather, learner autonomy appears to be more substantially influenced by individual and contextual variables, including motivation, metacognitive skills, and institutional support. The study highlights the importance of designing inclusive, learner-centered instructional strategies that foster autonomy for all students, irrespective of gender. In general, these findings contribute to the growing body of research emphasizing that learner autonomy is a dynamic, developable construct shaped primarily by educational practices rather than demographic differences.